Additions to Sphaeronemoura (Plecoptera: Nemouridae) from Oriental China - Li, Weihai; Li, Wenliang; Yang, Ding (Zootaxa, 2020)
A new species of the Amphinemurinae genus Sphaeronemoura is described, S. multicurvata sp. n., from Sichuan Province of southwestern China. The relationships with other related species are discussed. Sphaeronemoura elephas (Zwick, 1974) is also for the first time reported from Jiangxi Province of southeastern China.